Opini Audit Pemoderasi Pengaruh Profitabilitas, Ukuran Perusahaan, Kepemilikan Institusional, Dan Komite Audit Terhadap Ketepatanwaktuan - Azhari, Fadhli; Nuryatno, Muhammad (Jurnal Ilmiah Akuntansi dan Bisnis, 2019)
The purpose of this research is to find the role of audit opinion as a moderator of the effects of profitability, firm size, institutional ownership, and audit committee on the timeliness of financial reporting on manufacturing companies listed on the Indonesia Stock Exchange between 2012 and 2016. Purposive sampling was used in this research to obtain 96 sample manufacturing companies. The data analysis technique that was used in this research is logistic regression. The hypothesis testing showed that profitability and firm size positively affects the timeliness of financial reporting. Meanwhile, institutional ownership and audit committee does not affect the timeliness of financial reporting. Audit opinion cannot moderate the effect of profitability, firm size, institutional ownership, and audit committee on the timeliness of financial reporting. Keywords: profitability, firm size, institutional ownership, audit committee, audit opinion, timeliness